The Effect of Anterior Crowding Toward Oral Hygiene Index-Simplified and Gingival Index Score - Obi, Applonia Leu; Variani, Ratih; Ayatullah, M Ibraar (Poltekkes Kemenkes Jakarta III, 2023)
Dental crowding is one form of malocclusion characterized by disparities between the size of the tooth and the arc dimension. It is commonly found in the anterior region. Keeping the crowded and misaligned tooth is hard, leading to more plaque accumulation and increasing the risk of gingival inflammation. This research aims to find the effects of anterior dental crowding on the Oral Hygiene Index-Simplified (OHI-S) and Gingival Index scores of Poltekkes Kemenkes Kupang students. This is a cross-sectional study performed by observational analytical study design. The population was the student of Poltekkes Kemenkes Kupang with anterior crowding. Using 70 samples were chosen using purposive sampling technique. The result showed that most of the students had moderate anterior crowding (45.7%), followed by mild crowding (30%) and severe crowding (20%). The chi-square test showed a significant effect of anterior crowding toward OHI-S (p=0.03) and GI scores (p=0.04). While Socio-economical aspect also showed a significant effect (p=0.00) on OHI-S scores. A significant effect of socioeconomic status was also recorded on GI score (p=0.00). An observation of the students' oral hygiene intention showed that they mostly had a moderate intention (72.9%) to keep their mouth clean, and the rest, 27.1% had high oral hygiene intention. This aspect also significantly affects their scores of OHI-S (p=0.00) and GI (p=0.01). This study concluded that anterior crowding, socioeconomic status, and oral hygiene intention can affect OHI-S and GI scores of the students of Poltekkes Kemenkes Kupang